A comprehensive UHPLC–MS/MS method for the analysis of endogenous and exogenous steroids in serum for anti‐doping purposes. Issue 11 (21st October 2022) - Langer, Tobias; Salamin, Olivier; Nicoli, Raul; Grabherr, Silke; Kuuranne, Tiia; Musenga, Alessandro
Abstract: In the context of steroid analyses, the use of blood could represent a valuable complement to urine. While the blood steroid profile is currently being established to aid unveiling testosterone (T) doping, this matrix is also well suited for detection of exogenous anabolic steroids and steroid esters. In this study, a method to determine a simplified blood steroid profile in combination with the direct detection of exogenous anabolic steroids and steroid esters using just one serum aliquot was developed to obtain a comprehensive analytical workflow. Following the first chromatographic analysis of endogenous and exogenous steroids, samples were derivatised with Girard's reagent T (GT) to improve the ionisation of steroid esters and re‐injected. The quantitative performance for T, androstenedione (A4) and 5α‐dihydrotestosterone (DHT) was evaluated and the method was validated for qualitative analysis of exogenous analogues with estimated limits of detection (LOD) between 50 and 500 pg/ml. To demonstrate the applicability of the method, samples collected from a clinical study with an oral administration of testosterone undecanoate (TU) to 19 male volunteers were then analysed. The individual serum steroid profiles with the endogenous markers T, A4 and DHT were established as well as the concentrations of TU. TU was detected in all 19 volunteers up to 24 h, while DHT represented the most promising biomarker in endogenous steroid profile for the detection of oral TU administration. These results showed that the selected approach to combine exogenous and endogenous steroid analysis has the potential to strengthen T doping detection in the future. Abstract : A method for the detection of endogenous and exogenous steroids, including steroid esters, in serum was developed. Samples from an oral tesosterone undecanoate administration study were analysed to demonstrate the applicability for anti‐doping purposes.